Analisis Perilaku Konsumen Membeli Jasa Asuransi (Penerapan Model Howard) - Untaja, Paulus Perey (IQTISHODUNA, 2010)
This research intends to predict factors that drive consumer to buying insurance policy, based on consumer behavior model by Howard. In main variable used is buying decision. In addition, this study also include information, brand image, confidence and atitude as the control variables. The analysis unit are exclusive policy insured in Biak region. The data collection by using questionaire. The t test in simple regression models are used to test hypoteses.Research finding about : first, information unsignificant to influence confidence and atitude, but statistically significant to influence brand image. Second, brand image are statistically significant to influence confidence and atitude. Third, confidence and atitude are statistically significant to influence buying decision.